Penerapan Autoregressive Integrated Moving Average untuk Prediksi Inflasi Kabupaten Jember - Niken Abellia; Marizsa Herlina (Jurnal Riset Statistika, 2025)
Abstract. Inflation is an economic phenomenon that causes a general and sustained increase in the prices of goods and services. One of the factors influencing inflation is the amount of money circulating in the economy. This study aims to forecast the inflation rate in Jember Regency using the Autoregressive Integrated Moving Average (ARIMA) model. The data used in this research are inflation data from January 2018 to July 2022 obtained from the Central Statistics Agency (BPS). The analysis results show that the ARIMA(0,0,1) model performs better in forecasting inflation compared to ARIMA(1,0,0), with a Mean Square (MS) value of 0.095562. The forecast for inflation from August to October 2022 indicates a gradual increase in inflation from 0.213897% in August to 0.258068% in October 2022. The findings of this study provide insights for policymakers to anticipate inflation fluctuations in Jember Regency. Abstrak. Inflasi merupakan fenomena ekonomi yang menyebabkan kenaikan harga barang dan jasa secara umum dan berkelanjutan. Salah satu faktor yang mempengaruhi inflasi adalah jumlah uang yang beredar. Penelitian ini bertujuan untuk meramalkan tingkat inflasi Kabupaten Jember menggunakan model Autoregressive Integrated Moving Average (ARIMA). Data yang digunakan adalah data inflasi Kabupaten Jember dari Januari 2018 hingga Juli 2022 yang diperoleh dari Badan Pusat Statistik (BPS). Hasil analisis menunjukkan bahwa model ARIMA(0,0,1) lebih baik dalam meramalkan inflasi dibandingkan dengan ARIMA(1,0,0), dengan nilai Mean Square (MS) sebesar 0,095562. Peramalan inflasi untuk Agustus hingga Oktober 2022 menunjukkan bahwa inflasi diperkirakan akan meningkat secara bertahap dari 0,213897% pada Agustus menjadi 0,258068% pada Oktober 2022. Hasil penelitian ini dapat memberikan wawasan bagi pengambil kebijakan dalam mengantisipasi fluktuasi inflasi di Kabupaten Jember.